Keterpaparan Materi Pornografi dan Perilaku Seksual Siswa Sekolah Menengah Pertama Negeri - Mariani, Ani; Bachtiar, Imam (UI Scholars Hub, 2010)
Pornographic exposure and sexual behavior of Junior High School (JHS) students were studied to determine pornographic epidemy in young shool children. The study was carried out using questioner survey for students at Grades 7-9 on four state JHS at the City of Mataram. The respondents were consisted of 36 classes or 1415 students. Results of the study show that 91 per cent of students have been exposed to pornographic materials. The exposure was different between males and females. The pornographic exposure of Grade 7 was different from 8 and 9 students showing the vulnerability of Grade 7 students. Cellular or mobile-phone is the most popular equipment of pornographic exposure. At present, the earliest time student exposed to pornographic materials is at Grade 5, and there is a tendency to become earlier in future. Sexual behaviors of JHS students were identified still in normal level; 14 per cent students have experienced masturbation, 45 per cent have had boy or girl friends, and 13 per cent have had mouth-kissed. No student has sexual intercourse. Sexual behavior pattern was found different among school-grades along with pornographic exposure. Proportion of female students having boyfriend is higher than male students having girlfriend. There is no strong evidence on JHS students of Mataram City that pornographic exposures have any effect on sexual behaviors.